Status of occupational protection in the COVID-19 Fangcang Shelter Hospital in Wuhan, China - Min Zhang; Lili Wang; Siyuan Yu; Guixin Sun; Han Lei; Wenjuan Wu (Emerging Microbes and Infections)
Staff and employees “Zero infection” has been achieved during the whole medical activities in the COVID-19 Fangcang Shelter Hospital in Wuhan, China. This study analyses the personnel and environmental protection status of the East–West Lake Fangcang Shelter Hospital. The HCWs were mostly composed of national medical rescue teams, from different provinces in China. Before the COVID-19 outbreak, 82.64% of the HCWs had already known the proper procedure of wearing masks and other personal protective equipment (PPE). For the total of 634 participants entering the inpatient areas, 99.8% of them took occupational protection trainings via various methods. By carefully training and supervision, most of them were competent to work in the inpatient areas six hours/d, three-four times/week. Besides, 7.8% experienced different types of occupational exposure, which mainly caused by the damage of PPE. Once exposed, the HCWs would disinfect skin or mucous in time. No SARS-CoV-2 RNA was detected in 48 air and environmental samples after regular disinfection and cleaning. To conclude, the bundle including intensive training, strengthened personal protection, strict environmental disinfection and timely remedial measures for occupational exposure had ensured the safety of the East–West Lake Fangcang Shelter Hospital.